Introduced Reptile Early Detection and Documentation Training: Instructor Guide - Steve A. Johnson; Monica McGarrity (EDIS)
WEC292, a 5-page illustrated fact sheet by Steve Johnson and Monica McGarrity, familiarizes trainers with the REDDy program and provides the resources necessary for presenting the course concept and basic instructions to potential trainees and answering their questions. Published by the UF Department of Wildlife Ecology and Conservation, August 2010.